Accuracy and precision of the kinetic analysis of drop jump performance - Palazzi, D.; Williams, B. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aims of this study were to quantify (a) the accuracy and precision of measuring drop jump (DJ) performance kinetically and (b) the influence of the starting technique on those values. A 14-camera 3D motion analysis system and the double force plate technique were used simultaneously to obtain vertical displacements of centre of mass (CM) for comparison. Ten physically active male subjects performed DJs with 3 different techniques: stepping forward, with a small jump upwards, and flexing one knee before dropping. In total, 90 DJs were analyzed, 30 of each type. Small bias was obtained showing good accuracy as well as small typical error for jump height in all starting techniques. Our data indicates that double force plate technique can be used confidently for DJ analysis regardless of the starting technique.